Lazzarato's 'political entrepreneur' revisited: the case of Noko Jeans - Karl Palmås (Journal of Innovation and Entrepreneurship, 2012)
This article revisits Maurizio Lazzarato's 1994 text on the strategies of the political entrepreneur in the context of Noko Jeans, a recent Sweden-based venture to produce jeans in North Korea, while simultaneously influencing the political regime in the country. After a brief introduction to the venture in question, the article reviews Lazzarato's discussion on political entrepreneurship, which interrogates how such entrepreneurial action concurrently generates consumer interest and political discussion, thus blurring the boundary between business and politics. The article then discusses Lazzarato's theoretical points in light of the empirical case of Noko Jeans, first on an analytical level, then in relation to a recent event in which the founders were interviewed. The review thus aims at a re-evaluation of Lazzarato's work, suggesting that his conceptualisation of political entrepreneurship may prove useful when describing phenomena such as Noko Jeans.
Keywords: 650; political entrepreneurship; social entrepreneurship; North Korea; Maurizio Lazzarato; Entrepreneurship-Ansatz; Social Entrepreneur; Schwedisch; Politisches Ziel; Bekleidungsindustrie; Nordkorea